Helical bias in supramolecular polymers accounts for different stabilities of kinetically trapped states. Issue 12 (2nd March 2022) - Ślęczkowski, Marcin L.; Mabesoone, Mathijs F. J.; Preuss, Marco D.; Post, Yorick; Palmans, Anja R. A.; Meijer, E. W.
Abstract: The idea to synthesize and self‐assemble nano‐graphenes with structural precision into supramolecular polymers is just one of Klaus Müllen's many pioneering contributions to the chemical sciences. To honor his impact in the field of polymer science, we here describe a study that combines experimental and computational methods in studying the stability of kinetically trapped states of supramolecular polymers. We show that the introduction of stereocenters in the sidechains allow helical supramolecular polymers based on chiral triphenylene‐2, 6, 10‐tricarboxamide monomers to escape a kinetic trap more efficiently than polymers based on their achiral analogs. Partial depolymerization of the kinetically trapped state by increasing the temperature followed by polymerization by lowering the temperature shows that monomers either polymerize on existing stacks or self‐nucleate to form the thermodynamically more stable state. Chiral monomers prefer the latter more than achiral monomers. Abstract :